The military influence on the political construction of Ecuadorian Indians during the twentieth century - Ortiz, Cecilia (2006)
This article’s thesis is that in Ecuador the Armed Forces have played an important role in the political organization of the indigenous peoples and their recent irruption into national politics. On January 21, 2000 the military head officers staged a coup d’etat using a sector of high rank officers, the Indian organizations and the social organizations. These officers intended to protect the status quo that had suffered a hard blow after the peace treaty with Peru, which disabled war as a discourse around which to rally for national unity. At the same time, the Indians use the Armed Forces as a way of gaining national presence in decision-making political spaces. This two-way dealing emerged from a military scheme that became apparent during the first decades of the twentieth century when the first signs of what would later become a multicultural nationalism came into view.